4-6m=(3m+14)-2(3m+5)

Simple and best practice solution for 4-6m=(3m+14)-2(3m+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-6m=(3m+14)-2(3m+5) equation:


Simplifying
4 + -6m = (3m + 14) + -2(3m + 5)

Reorder the terms:
4 + -6m = (14 + 3m) + -2(3m + 5)

Remove parenthesis around (14 + 3m)
4 + -6m = 14 + 3m + -2(3m + 5)

Reorder the terms:
4 + -6m = 14 + 3m + -2(5 + 3m)
4 + -6m = 14 + 3m + (5 * -2 + 3m * -2)
4 + -6m = 14 + 3m + (-10 + -6m)

Reorder the terms:
4 + -6m = 14 + -10 + 3m + -6m

Combine like terms: 14 + -10 = 4
4 + -6m = 4 + 3m + -6m

Combine like terms: 3m + -6m = -3m
4 + -6m = 4 + -3m

Add '-4' to each side of the equation.
4 + -4 + -6m = 4 + -4 + -3m

Combine like terms: 4 + -4 = 0
0 + -6m = 4 + -4 + -3m
-6m = 4 + -4 + -3m

Combine like terms: 4 + -4 = 0
-6m = 0 + -3m
-6m = -3m

Solving
-6m = -3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '3m' to each side of the equation.
-6m + 3m = -3m + 3m

Combine like terms: -6m + 3m = -3m
-3m = -3m + 3m

Combine like terms: -3m + 3m = 0
-3m = 0

Divide each side by '-3'.
m = 0

Simplifying
m = 0

See similar equations:

| 1.2t+3.4=-1.0 | | 6y+14=-7-y | | 11-3(x-1)=6+x | | 4(4x-3)-6x=x | | 3-2x(x+1)=x-2 | | -x+4x+1=3x-1+2 | | -2x+2x+4=3x-2x+2 | | 6-8x-3=-39+6x-14 | | 80+x=180 | | -9(x-7)-6=57 | | -20-9b+1=16b+20 | | 2(6x+5)=3x-26 | | 3-19p=-18p+20 | | -6w-12+2w=28 | | (10/3)/(2/21) | | -4/-5y=72 | | -3m=-6-5m | | 52/650 | | (1/4x-6)=(2/3x+3) | | 4u=3u-8 | | 2[3x-(4x-8)]=5(x-8) | | 3x+15=11+5x | | -7x+16=8(5x+2) | | -8p=176 | | 4(x+2)/6 | | 3+5(-8a-1)=-6-(3a-4) | | 0.15-0.01(x+1)=-0.03(2-x) | | (-2x/11)=66 | | 7x+3=2(3x+1)-x+8 | | x+6=15-x | | 13/6+x=6 | | 16n^2-8n-15=0 |

Equations solver categories